The duration of union membership: An empirical study - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2006)
Thanks to direct access to union databanks, this paper can answer two new questions in Industrial Relations: how long union membership lasts and what are the determinants of its duration. This also allows to conceptualize union membership as a much more dynamic phenomenon than in previous studies, where it was considered a static situation whose causes or eþects were to be investigated. Survival analysis applied to a sample of 48705 workers highlights that union membership duration is a positive, though declining, function of age. Furthermore, women, "flexible" workers, foreign ones and those working in cities tend to show less attachment to union membership than the other workers.
Keywords: 330; Gewerkschaft; Mitgliedschaft; Dauer; Gewerkschaftlicher Organisationsgrad; Italien